Interpresentasi Estetika Fetishisme Terhadap Hewan Yang Sudah Mati Dalam Seni Patung - Iqbal, Mochammad; Ruta, I Made; Mudana, I Wayan (PROGRAM STUDI SENI MURNI ISI DENPASAR, 2022)
Commodity dimensions in art include exchange value, commercial value, valorization, commodity fetishism, market logic. Reading art through the commodity dimension is an attempt to reveal the economic value contained in the work of art. This value is not only contained in works of art, but also has a deterministic power to build and organize art. art that is part of a commodity—resulting in an aesthetic category, called “commodity aesthetics”. This is the kind of aesthetic, which builds attraction through the workings of the